2001
DOI: 10.1186/cc1310
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of neuro-trauma. A 1 year retrospective study in an intensive care unit

Abstract: P14 Facial continuous positive airway pressure therapy for cardiogenic pulmonary oedema: a study of its efficacy in an emergency department setting within the UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The most common causes of trauma are in-vehicle traffic accidents, falls, pedestrians, motorcycle accidents and sharp object injuries [15,[24][25][26][27]. In our study, the most common causes were in-vehicle traffic accidents (33.7%), falls (28.7%) and extravehicular traffic accidents (24.8%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The most common causes of trauma are in-vehicle traffic accidents, falls, pedestrians, motorcycle accidents and sharp object injuries [15,[24][25][26][27]. In our study, the most common causes were in-vehicle traffic accidents (33.7%), falls (28.7%) and extravehicular traffic accidents (24.8%).…”
Section: Discussionmentioning
confidence: 53%
“…Studies indicate that low GCS in trauma is important in predicting mortality and the best predictive power would be 5.5 [1,6]. In similar studies, Mpe et al [27] reported that GCS values of 4 or less at admission to the intensive care unit were poor prognosis. Our mean GCS scores in the surviving group was higher, similar to the reports in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…[28] Teoh et al [29] studied 1390 patients who were treated in intensive care units and followed up for 4 years, and found a significant relationship between the GCS score and mortality. Mpe et al [30] conducted a retrospective study and found that the mortality rate was high in trauma patients, the prognosis of patients with a GCS value of 4 and below at admission to the intensive care unit was poor, and that very few patients with low GCS values were able to fully recover. [30] In the present study, the mean GCS of patients who died was low; 17 of the 18 cases of mortality had a GCS below 9.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Chalfie et al (11) showed that delays in admission to emergency services negatively affect the duration of hospital stay and mortality. Patient outcomes heavily depend on the timely intervention for critically ill patients (12)(13)(14)(15)(16)(17)(18). Thus, prolonged ICU admission time may be an important factor affecting the patient outcomes.…”
Section: Discussionmentioning
confidence: 99%